Effects of Student-Team -Achievement-Division Instructional Strategy On Upper Basic School Convergent And Divergent Students’ Interest In Basic Science In Benue State (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examined the effects of Students-Team-Achievement-Division Instructional Strategy on upper basic Convergent and Divergent students’ interest, in Basic Science in Benue state. The study was guided by two (2) objectives, two (2) research questions and two (2) hypotheses. Quasi-experimental pre-test, post-test control group research design was used for the study. The sample of this study constituted of one hundred and sixty (160) upper basic eight (8) students from four (4) co-educational upper basic schools in Makurdi Local Government Area Benue State. Multi-stage sampling techniques were used in drawing the respondents. One instrument titled: Basic Science Interest Questionnaire (BSIQ) was used for the study. In analyzing the data obtained from the respondents, mean, Mann Whitney Test and Kruskal –Wallis test were employed. The findings of the study revealed that: there was significant difference between the mean interest scores of Convergent and Divergent students taught Basic Science using STAD and those taught using Conventional method. There was no significant difference between the mean interest scores of male and female Convergent and Divergent students taught Basic Science using STAD. Based on the findings of the study, it was recommended that, since STAD was found to be effective in enhancing students’ interest it should be adopted by teachers as a teaching strategy in basic science.